The wave of unemployment amongst South African youths: belonging to a political organisation as a way of escape? - Adetiba, Toyin Cotties; Qwabe, Nqobile Thandolwethu (Penerbit Universiti Kebangsaan Malaysia, 2020)
With the rise of unemployment in South Africa, the youth has been looking for a way out, building up a stereotype that being part of a political movement would secure them an automatic employment. This research examines if this phenomenon proves valid, whilst assessing factors that have recently played a role in the increment of unemployment in South Africa, and more or less how the stereotype of political employment can be discredited; through both quantitative and qualitative research conducted in a small township of Esikhawini in the province of KwaZulu-Natal (KZN) of South Africa, the study looks at how political and non-political participants see belonging to a political organisation vis-à-vis unemployment amongst South African youths, concluding that South African government needs to create an enabling environment where the creation of employment opportunities will thrive.